Omnibus Law and the Paradox of Progress: A Critical Discourse Analysis of Labor Rights and Investment Flexibility in Post-Reform Indonesia - Wiraatma, Azzam Haidar; Anggraini, Kaylaresta Ratnadewi (Indonesia Discourse, 2025)
This study examines the legislative discourse surrounding Indonesia’s Job Creation Law (Omnibus Law), focusing on the inherent tension between attracting foreign direct investment and upholding constitutional labor protections. Since the 1998 Reformation, Indonesia has struggled to balance neoliberal economic aspirations with social justice mandates. Utilizing Critical Discourse Analysis (CDA) on parliamentary debates, policy white papers, and judicial review transcripts, this research identifies a dominant narrative of "emergency economic acceleration" used to justify the erosion of severance pay, job security, and environmental safeguards. The findings suggest that the Omnibus Law represents a significant shift toward a "flexicurity" model that lacks the robust social safety nets found in Western counterparts, effectively creating a paradox where legal progress for capital mobility results in legal regression for labor rights. This paper argues that such legislative strategies may undermine long-term democratic stability by deepening socio-economic inequality. It provides a cautionary case study for other emerging economies attempting to reform complex legal landscapes through high-speed, multi-sectoral legislation.